Answer :

The given A.P is


The simplified A.P is



Here a=


d= =


Sn = (2a + (n–1) d)


= (2 + (n–1))


= /2 (1 + n)


= n (n + 1)/

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Arithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these Questions56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses